Use of the central catheter for peripheral insertion in newborns: analysis of indication for removal - Maria Aparecida Baggio; Maycon Hoffmann Cheffer; Mayara Aparecida Passaura da Luz; Michelle de Marchi Sanches; Rosilene Berres (Universidade Federal do Ceará, 2019)
Objective: to analyze the use of the central catheter for peripheral insertion in newborns. Methods: retrospective, documentary study. For data collection, we used an instrument to record and follow the central catheter for peripheral insertion. Analysis performed using descriptive statistics to obtain absolute, relative, minimum and maximum values, standard and mean deviations, and chi-square test for K-proportions for qualitative variables. Results: we analyzed 383 records. The catheter was mainly indicated for administration of antibiotic therapy (46.5%). The most accessed vessel was the cephalic vein (23.5%). The most frequent complication was progression (6.8%), with prevalence of removal due to end of treatment/indication (25.3%). Conclusion: catheter used mainly for antibiotic therapy administration; cephalic vein mostly accessed, using fentanyl to mitigate pain and discomfort; progression, mostly incident complication; and higher removal rate due to end of treatment/indication.